La «bancarotta della scienza». Il giovane Gramsci e la crisi del positivismo - Di Meo, Antonio (International Gramsci Journal, 2023)
Antonio Gramsci found himself thinking and acting in a field of highly acute intellectual tensions, in which he very quickly understood and soon came up against the limits of the Marxism of his time. Amongst those fields of knowledge regarded as being in crisis at the turn of the twentieth century were science and the philosophy – positivism – that to a large extent had up to then gone alongside it; this could not but have its repercussions within the socialism of Marx and Engels that, in comparison with other types, had acquired a distinctive nature in so far as it was ‘scientific’. There was, then, discussion of the ‘bank-ruptcy of science’ most of all in the wake of a celebrated article in 1895 by the literary scholar Ferdinand Brunetière, in response to the secularist positions held by Ernest Renan. From this stemmed a wide-ranging debate touching Gramsci, then still at high school, and the Italian culture of his time; significant developments of this may be noted in his later writings right up to the Prison Notebooks, in particular as regards the ideology of ‘progress’.